2015
DOI: 10.1016/j.jchf.2014.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Diabetes on Epidemiology, Treatment, and Outcomes of Patients With Heart Failure

Abstract: The prevalence of patients with concomitant heart failure (HF) and diabetes mellitus (DM) continues to increase with the general aging of the population. In patients with chronic HF, prevalence of DM is 24% compared with 40% in those hospitalized with worsening HF. Patients with concomitant HF and DM have diverse pathophysiologic, metabolic, and neurohormonal abnormalities that potentially contribute to worse outcomes than those without comorbid DM. In addition, although stable HF outpatients with DM show resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
170
0
14

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 280 publications
(187 citation statements)
references
References 54 publications
3
170
0
14
Order By: Relevance
“…It is recommended that patients with HF-REF and diabetes mellitus are treated with ACEi/angiotensin receptor blocker and β-blockers, supplemented with MRAs if symptoms persist [21,37,38,39,40,41,42,43]. Outpatients with stable HF have a similar response to established HF treatment, irrespective of whether they have diabetes mellitus or not [44]. However, recent trials with novel therapies suggest that HF patients with diabetes might be more prone to developing adverse effects and that drugs may have different effects on HF patients with and without diabetes mellitus [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…It is recommended that patients with HF-REF and diabetes mellitus are treated with ACEi/angiotensin receptor blocker and β-blockers, supplemented with MRAs if symptoms persist [21,37,38,39,40,41,42,43]. Outpatients with stable HF have a similar response to established HF treatment, irrespective of whether they have diabetes mellitus or not [44]. However, recent trials with novel therapies suggest that HF patients with diabetes might be more prone to developing adverse effects and that drugs may have different effects on HF patients with and without diabetes mellitus [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…Willey et al (2014) established that hypertension and diabetes have important effects on the burden of stroke, especially in individuals b 80 years of age and Hispanics. In addition, Dei Cas et al (2015) reported that the frequency of patients with heart failure and DM will increase with the general aging of the population. A specific cellular type involved with the development of CVD is the endothelial cell.…”
Section: Dm Cardiovascular Disease (Cvd) and Agingmentioning
confidence: 99%
“…The prevalence of DM in patients with heart failure (HF) is extremely high (occurring in up to 40–45% of these patients) 7, 8. Not surprisingly, the burden of morbidity and mortality associated with CHF and DM represents, to date, a major challenge for the prospective sustainability of contemporary healthcare systems 8, 9, 10, 11…”
Section: Introductionmentioning
confidence: 99%